Ethnicity and irredentism impediments of political and religious unity - Shuriye, Abdi Omar (Institute of Islamic Understanding Malaysia, 2005)
Ethnicity, irredentism and religion based politics persist to be some of the most complex issues in ethno-political thought in governance systems of the world; as nations struggle to nurture harmonious political system ethnicity seem perturbing; indeed, developed nations face ethnic based conflicts and religious intensity. Though the term “ethnic conflict” became a common term decades ago in the political scenario; it nonetheless embodies vague denotation. Likewise tribal conflicts; conventional political conundrum in the Muslim world, (Somalia, Afghanistan and others) have been perplexed with ethnic and religious conflicts. Irredentism, secession and separatism are other forms of political obstruction in the Muslim world that impede political and religious unity. The growth of scholarly publications on religio-ethnicity particularly in the field of political science in late 1990s emphasized the societal aspect of the issue and made nominal allusion to conflicts based on religious and ethnic background; a tendency that loiters to be the central focus of numerous researches for decades to come. The purpose of this paper is to conceptualize the effect of religio-ethno-conflicts and related state-of-affairs including irredentism, on Muslim unity. As the role of ethnicity and religion became so visible in the political system of Muslim nations various social theorists conjecture that ethnic and religious conciousness would remain virtually persistent political glitch and will not vanish as a result of globalization; as earlier academic prophecy held. The paper further intends to explore the relationship between conflicts with ethnic milieu and religion predisposed ones. In another context it investigates the role of irredentism; a dominant component of ethnicity in the history of ethno-religious conflicts.